Reversal of multidrug resistance by magnetic Fe3O4 nanoparticle copolymerizating daunorubicin and MDR1 shRNA expression vector in leukemia cells - Bao-an Chen (Dove Medical Press, 2010)
Bao-an Chen1, Pei-pei Mao1, Jian Cheng1, Feng Gao1, Guo-hua Xia1, Wen-lin Xu2, Hui-lin Shen2, Jia-hua Ding1, Chong Gao1, Qian Sun1, Wen-ji Chen1, Ning-na Chen1, Li-jie Liu3, Xiao-mao Li4, Xue-mei Wang51Department of Hematology, The Affiliated Zhongda Hospital, Clinical Medical School, Southeast University, Nanjing, People’s Republic of China; 2Department of Hematology, The Affiliated People’s Hospital, Jiangsu University, Zhenjiang, People’s Republic of China; 3Institution of Physiology, Southeast University, Nanjing, People’s Republic of China; 4Department of Physics, University of Saarland, Saarbruecken, Germany; 5State Key Lab of Bioelectronics (Chien-Shiung Wu Laboratory), Southeast University, Nanjing, People’s Republic of ChinaAbstract: In many instances, multidrug resistance (MDR) is mediated by increasing the expression at the cell surface of the MDR1 gene product, P-glycoprotein (P-gp), a 170-kD energy-dependent efflux pump. The aim of this study was to investigate the potential benefit of combination therapy with magnetic Fe3O4 nanoparticle [MNP (Fe3O4)] and MDR1 shRNA expression vector in K562/A02 cells. For stable reversal of “classical” MDR by short hairpin RNA (shRNA) aiming directly at the target sequence (3491–3509, 1539–1557, and 3103–3121 nucleotide) of MDR1 mRNA. PGC silencer-U6-neo-GFP-shRNA/MDR1 called PGY1–1, PGY1–2, and PGY1–3 were constructed and transfected into K562/A02 cells by lipofectamine 2000. After transfected and incubated with or without MNP (Fe3O4) for 48 hours, the transcription of MDR1 mRNA and the expression of P-gp were detected by quantitative real-time PCR and Western-blot assay respectively. Meanwhile intracellular concentration of DNR in K562/A02 cells was detected by flow cytometry (FCM). PGC silencer-U6-neo-GFP-shRNA/MDR1 was successfully constructed, which was confirmed by sequencing and PGY1–2 had the greatest MDR1 gene inhibitory ratio. Analysis of the reversal ratio of MDR, the concentration of daunorubicin (DNR) and the transcription of MDR1 gene and expression of P-gp in K562/A02 showed that combination of DNR with either MNP (Fe3O4) or PGY1–2 exerted a potent cytotoxic effect on K562/A02 cells, while combination of MNP (Fe3O4) and PGY1–2 could synergistically reverse multidrug resistance. Thus our in vitro data strongly suggested that a combination of MNP (Fe3O4) and shRNA expression vector might be a more sufficient and less toxic anti-MDR method on leukemia. Keywords: K562/A02 cell line, multidrug resistance, magnetic nanoparticle of Fe3O4, recombinant plasmid vector PGY1–2